Genetic Polymorphism and Molecular Epidemiology of Leishmania (Viannia) braziliensis from Different Hosts and Geographic Areas in Brazil - Cupolillo, Elisa (American Society for Microbiology, 2003)
Numerical zymotaxonomy and variability of the internal transcribed spacers (ITS) between the small and large subunits of the rRNA genes were used to examine strain variation and relationships in natural populations of Leishmania (Viannia) braziliensis. A total of 101 strains from distinct hosts and Brazilian geographic regions were assigned to 15 zymodemes clustered in two major genetic groups. The great number of isolates (48.5%) placed in zymodeme IOC/Z-27 were collected on the Atlantic coast. The high molecular diversity found in populations in the Amazon Basin was related to the great number of sandfly vector(s) in that region. The results of the restriction fragment length polymorphism analysis of the ITS depicted considerable intraspecific variation. Genotypic groups A, B, and C contained 39, 40, and 22 isolates, which were divided into 16, 10, and 15 genotypes, respectively. The genetic polymorphism observed demonstrates the degree of diversity of L. (V.) braziliensis strains from different regions where they are endemic. The results reinforce the clonal theory for Leishmania parasites showing the genetic diversity of this pathogen and an association of L. (V.) braziliensis genotypes with specific transmission cycles, probably reflecting an adaptation of different clones to the vector species involved.